Population density and abundance of basking sharks Cetorhinus maximus in the lower Bay of Fundy, Canada - AJ Westgate; HN Koopman; ZA Siders; SNP Wong; RA Ronconi (Endangered Species Research, 2014)
The conservation status of basking sharks Cetorhinus maximus in eastern Canadian waters is not clearly understood, in part because population densities and abundances have not been recently estimated. On September 11, 2009 and 2011, aerial surveys of basking sharks were conducted in the lower Bay of Fundy, Canada. Flyover tests of a wooden shark silhouette revealed that basking sharks were visible to a depth of 5 m. The proportion of time basking sharks were estimated between 0 and 5 m depth (availability bias) was 19% based on 1252 h of time-depth recorder data from 13 free-swimming sharks. During the 2 surveys, 26 sharks were sighted. Using the program Distance, availability bias corrected densities of 0.0513 sharks km-2 (2009, 95% CI = 0.0188 to 0.1402) and 0.0598 sharks km-2 (2011, 95% CI = 0.0358 to 0.1001) were reported. This corresponds to abundance estimates of 542 sharks (2009, 95% CI = 198 to 1482) and 632 sharks (2011, 95% CI = 377 to 1058) occupying a 10570 km2 area in the lower Bay of Fundy. Abundance was far lower than previously estimated using indirect methods and untested assumptions (Bay of Fundy = 4200 sharks). Previously published habitat suitability models for basking sharks in the Bay of Fundy predict heterogeneous habitat use, which would lower the overall abundance estimate. This lower population estimate for the Bay of Fundy, coupled with a very limited capacity to respond to significant levels of anthropogenic mortality, raises concerns about the conservation status of eastern Canadian basking sharks.